O padrão de compressão de video MPEG moving picture experts group - Arabura, Gustavo dos Santos [UNESP] (2012)
This work focuses on the study of video compression standard MPEG. To this end, a study was undertaken starting from the basics of digital video, addressing the components necessary for the understanding of the tools used by the video coding standard MPEG. The Motion Picture Experts Group (MPEG) was formed in the late '80s by a group of experts in order to create international standards for encoding and decoding audio and video. This paper will discuss the techniques present in the video compression standard MPEG, as well as its evolution. Will be described in the MPEG-1, MPEG-2, MPEG-4 and H.264 (MPEG-4 Part 10), however, the last two will be presented with more emphasis, because the standards are present in most modern video technologies, as in HDTV broadcasts